Recording injuries only during winter competitive season underestimates injury incidence in elite athletes of the French ski federation: a two-year prospective cohort study - Bouscaren, N.; Guyon, A.; Jesus, S. (British Journal of Sports Medicine, 2021)
Background The implementation of an optimal injury prevention program is based primarily on a solid epidemiological injury surveillance system. Current epidemiological studies in skiing disciplines of International Skiing Federation are limited to retrospective surveys only on winter competitive season (WCS).